Exploration of ADHD Subtype Definitions and Co-Occurring Psychopathology in a Missouri Population-Based Large Sibship Sample - Reiersen, Angela M; Todorov, Alexandre A (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2013)
Background: There is some debate regarding the utility of Attention-Deficit/ Hyperactivity Disorder (ADHD) subtypes as currently defined. Differences in co-occurring psychopathology among subtypes would support the validity of subtype definitions. Objective: To explore how ADHD subtype relates to co-occurring psychopathology in a large population-based sample of children and adolescents (n=5744). Method: Parents completed the Strengths and Weaknesses of ADHD-symptoms and Normal behavior (SWAN) questionnaire, the Child Behavior Checklist (CBCL) and the Social Responsiveness Scale (SRS). Methods including discriminant analysis, principal components analysis, and fractional polynomial regression were used to examine the relationship between ADHD diagnostic subtypes and co-occurring psychopathology. Results: Children with different ADHD subtypes show differences on several CBCL subscales. A combination of CBCL subscales and SRS score had good ability to discriminate ADHD subtypes. Conversely, for the same overall number of ADHD symptoms, individuals who present with both inattentive and hyperactive/impulsive symptoms exhibit higher severity of co-occurring psychopathology on a summary measure derived from principal components analysis of the CBCL subscales and SRS. This includes some subjects who fail to meet the DSM-IV-TR ADHD symptom criterion due to having less than 6 inattentive and less than six hyperactive-impulsive symptoms, yet have ADHD symptom severity similar to those with the inattentive or hyperactive-impulsive subtype. Conclusions: Several convergent lines of analysis provide support for the continued use of ADHD subtypes (or current presentation symptom profiles), as evidenced by differences in co-existing psychopathlogy. We also found that current diagnostic criteria may fail to identify a potentially impaired group of individuals who have low-to-moderate levels of both inattention and hyperactivity/impulsivity. Under the upcoming DSM-5, it will be important for clinicians to consider the option of giving an ADHD “not elsewhere classified” diagnosis to such children.